Contributions of Digital Technologies in the Health Teacher Training Course (Research, Society and Development, 2020)
Distance education has also been a strategy employed in continuing education processes to enable and qualify teachers' work. The aim of this study was to identify what were the contributions regarding the development of a continuing education course, mediated by digital technologies, to teachers of Basic Education. It is a qualitative research, developed in three stages: questionnaire application to know a profile of the participants; development of a continuing teacher training course on health using the Hangout platform; and evaluation of the training process. Fifty-four Basic Education teachers from two municipalities on the western border of the state of Rio Grande do Sul participated. The method of analysis was the content analysis type. From the results obtained, it was verified that the implications were linked to the profile of the participating teachers and also to the use of digital technologies, such as the Hangout, to mediate and develop the proposal of formative actions with the teachers. Potentialities and weaknesses were identified about the development of the course mediated by digital technology. These were important in order to outline new strategies that meet the demands of teachers continuing education, aiming to improve and qualify the training process as a whole.